(untitled) (Journal of Science and Technology, 2016)
Law is an inescapable context within which we all live. This is the position whether we live in a Nation like Ghana or in an academic community like a University. So it comes about that the University of Science and Technology, Kumasi, apart from being enveloped by general public laws of Ghana, has its own laws, rules and regulations. One of such laws is Statute 25. The importance of this Statute as far as discipline in the University is concerned can hardly be doubted. But it does not appear that there is maximum comprehension of the express provisions, implications and ramifications of this law among the members and staff of the University commensurate with its importance. This paper therefore attempts to put this particular statute into perspective, for the elucidation and, edification of all concerned. The aim in doing this .is to press home the point that it is eminently desirable that we discharge our respective duties properly, competently and efficiently at all times.